2021
DOI: 10.3390/antiox10040549
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Serum γ-Glutamyltransferase as a Prognostic Biomarker in Patients with Genitourinary Cancer

Abstract: γ-Glutamyltransferase (GGT), a membrane-bound enzyme, contributes to the metabolism of glutathione (GSH), which plays a critical physiological role in protecting cells against oxidative stress. GGT has been proposed as a biomarker of carcinogenesis and tumor progression given that GGT activity is important during both the promotion and invasion phases in cancer cells. Moreover, GGT expression is reportedly related to drug-resistance possibly because a wide range of drugs are conjugated with GSH, the availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 92 publications
(150 reference statements)
0
28
0
Order By: Relevance
“…GGT1 is a member of the GGT family, which also includes other proteins, such as GGT2, GGT3P, GGT4P, GGT5, GGT6, GGT7, and GGT8P. Among these, GGT1 and GGT5 are the only two enzymes with catalytic activity ( Takemura et al, 2021 ), and the catalytic rate of GGT1 is approximately 46 times faster than that of GGT5 ( Wickham et al, 2011 ). Therefore, GGT1 is the main catalytically active enzyme in the GGT family.…”
Section: Discussionmentioning
confidence: 99%
“…GGT1 is a member of the GGT family, which also includes other proteins, such as GGT2, GGT3P, GGT4P, GGT5, GGT6, GGT7, and GGT8P. Among these, GGT1 and GGT5 are the only two enzymes with catalytic activity ( Takemura et al, 2021 ), and the catalytic rate of GGT1 is approximately 46 times faster than that of GGT5 ( Wickham et al, 2011 ). Therefore, GGT1 is the main catalytically active enzyme in the GGT family.…”
Section: Discussionmentioning
confidence: 99%
“…GGT1 and GGT5 act on gamma-glutamyl residue reversibly from various gamma-glutamyl residue-containing compounds [ 37 ]. The cleaved gamma-glutamyl residue is transferred to a variety of substrates [ 38 ], which are not limited to glutathione (GSH), GSH disulfide (GSSG), the GSH-xenobiotics made by glutathione-S-transferases, leukotriene C 4 , S-nitroso-GSH [ 39 ], drug metabolites, and neuroactive compounds [ 40 43 ]. Thus, GGT further expands its enzymatic activity by generating diverse compounds with other physiological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Serum GGT could be a specific biomarker reflecting the tumor GGT expression, given that most PC specimens (79%) showed moderate to strong GGT expression in the immunohistochemical analysis ( Table 5 ) and that serum GGT could increase in patients with advanced cancer with GGT overexpression according to a recent systematic review [ 15 ]. GGT is an ectoenzyme known to contribute to the metabolism of GSH, playing a critical physiological role in protecting cells against oxidative stress [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort of a middle-aged, male population demonstrated that serum GGT was positively and independently associated with future risk of PC over long-term follow-up [ 14 ]. A recent systematic review suggested that GGT could be detected in the peripheral blood of patients with advanced genitourinary cancer particularly when cancer cells had high GGT expression, the disease was advanced, or the tumor burden was heavy [ 15 ]. Although the source of serum GGT in men with mCRPC is largely unknown, it could be derived from PC cells, given that higher immunopositivity of GGT was observed in prostatic adenocarcinomas than in normal prostatic cells based on previous immunohistochemical analysis [ 16 ], and that cultured PC cells released soluble GGT complexes into supernatants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%